2013
DOI: 10.1371/journal.pone.0061551
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Mitochondrial Target of Thiazolidinedione Insulin Sensitizers (mTOT)—Relationship to Newly Identified Mitochondrial Pyruvate Carrier Proteins

Abstract: Thiazolidinedione (TZD) insulin sensitizers have the potential to effectively treat a number of human diseases, however the currently available agents have dose-limiting side effects that are mediated via activation of the transcription factor PPARγ. We have recently shown PPARγ-independent actions of TZD insulin sensitizers, but the molecular target of these molecules remained to be identified. Here we use a photo-catalyzable drug analog probe and mass spectrometry-based proteomics to identify a previously un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

13
161
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 153 publications
(175 citation statements)
references
References 30 publications
13
161
0
1
Order By: Relevance
“…Although it was later revealed that the main mitochondrial binding site of pioglitazone was the Mpc mitochondrial pyruvate carrier complex (6), this initial observation launched a series of studies to unravel the molecular function of the mNEET protein. mNEET belongs to a family of three proteins exhibiting a CDGSH domain, together with miner1 and miner2.…”
mentioning
confidence: 99%
“…Although it was later revealed that the main mitochondrial binding site of pioglitazone was the Mpc mitochondrial pyruvate carrier complex (6), this initial observation launched a series of studies to unravel the molecular function of the mNEET protein. mNEET belongs to a family of three proteins exhibiting a CDGSH domain, together with miner1 and miner2.…”
mentioning
confidence: 99%
“…TZD activation of the energy status-sensing, catabolism driver AMP-activated protein kinase (AMPK) [26], is also mimicked by UK5099. In another report, MCP1 and MCP2 were identified as mitochondrial proteins that could be chemically crosslinked to TZD [27] in a manner that could be blocked by UK5099. These authors also showed that TZDs altered the incorporation of 13 C-labeled carbon from glucose into acetyl CoA.…”
Section: Aspects Of Metabolic Regulation Unveiled By Mpc Inhibitionmentioning
confidence: 99%
“…A new mitochondrial drug target has been identified that provides an opportunity to treat metabolic diseases by changing the way pyruvate is metabolized, and this may have implications for treating diseases as diverse as Parkinson's disease and liver disease. Mitochondrial target of thiazolidinediones (mTOT)1, 2, 3 modulators have been selected for their ability to bind to and modulate the activity of the mTOT, which was subsequently identified as the mitochondrial pyruvate carrier (MPC). The MPC is a heterologous complex composed of two proteins, MPC1 and MPC2, in the inner mitochondrial membrane 4, 5.…”
mentioning
confidence: 99%